Implicações do suporte social percebido e do conflito trabalho-família em agentes comunitários de saúde - Machado, Vanessa Cadore (2017)
This research aimed to evaluate whether there is a correlation between social support and conflict between work and family. It is a cross-sectional and correlational study with a quantitative approach that used the Work-Family Conflict Scale and the 2-Way Social Support Scale (2-Way SSS). The participants were 139 workers who act as community health agents in four cities from Rio Grande do Sul. In order to analyze the data, we used descriptive statistics, parametric statistics and Pearson’s Correlation. The results between the correlations of the scales were significant, showing conflict between the work and the families of the community health agents. Therefore, we conclude that the intensification of demands in professional and family domains would have harmful consequences on both individual well-being and on aspects related to the performance of work activities.